2022
DOI: 10.1177/11782218221114971
|View full text |Cite
|
Sign up to set email alerts
|

Cue Reactivity to Electronic Cigarettes: A Systematic Review

Abstract: Cue reactivity to Electronic Nicotine Delivery Systems (ENDS) has been studied by several researchers, yet the variability in user types (smokers, former smokers, dual users, exclusive ENDS users) and ENDS designs used between the studies may have undermined consistent results. This systematic review aims to give an overview of ENDS cue reactivity and how smoking status and device design may moderate this. A systematic search of Medline, Embase, Web of Science, PubMed and Cochrane was completed. All studies wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 86 publications
0
2
0
Order By: Relevance
“…Conklin et al (2015) have shown that cue reactivity predicts actual smoking behavior. Moreover, a systematic review of the literature on cue reactivity to electronic nicotine delivery systems (ENDS) reported that most of the studies reviewed found that ENDS related cues elicits craving for ENDS, and this finding was consistent across both cigarette smokers and ENDS users and device designs (Keijsers et al, 2022). These findings may extend to illicit drugs; cigarettes elicit cue reactivity among crack cocaine users whose route of administration is smoking (Reid et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…Conklin et al (2015) have shown that cue reactivity predicts actual smoking behavior. Moreover, a systematic review of the literature on cue reactivity to electronic nicotine delivery systems (ENDS) reported that most of the studies reviewed found that ENDS related cues elicits craving for ENDS, and this finding was consistent across both cigarette smokers and ENDS users and device designs (Keijsers et al, 2022). These findings may extend to illicit drugs; cigarettes elicit cue reactivity among crack cocaine users whose route of administration is smoking (Reid et al, 1998).…”
Section: Discussionmentioning
confidence: 96%
“…In relation to vaping triggers, unlike previous reports [41], in our study, neither passive exposure to vaping nor vaping advertisement appeared to trigger a desire for vaping or smoking. This applies mainly to dual users, who also indicated that, when seeing others smoking tobacco cigarettes, this may trigger their desire for smoking, which sometimes, maybe mitigated with vaping [42]. In terms of olfactory triggers, only fruit e-liquids were found to have some effect.…”
Section: Discussionmentioning
confidence: 98%